Windows into the soul: surveillance and society in an age of high technology - Marx, Gary T. (The University of Chicago Press, 2016)
Concepts: the need for a modest but persistent analyticity -- Defining the terms of surveillance studies -- So what's new? : classifying means for change and continuity -- So what's old?: classifying goals for continuity and change -- The stuff of surveillance: varieties of personal information -- Social processes -- Social processes in surveillance -- A tack in the shoe and taking the shoe off: resistance and counters to resistance -- Culture and contexts -- Work: the omniscient organization measures everything that moves -- Children: slap that baby's bottom, embed that ID chip, and let it begin -- The private within the public: psychological report on Tom I. Voire -- A mood apart: what's wrong with Tom? -- Government and more: a speech by Hon. Rocky Bottoms to the Society for the Advancement of Professional Surveillance -- Ethics and policy -- Techno-fallacies of the information age -- An ethics for the new (and old) surveillance -- Windows into hearts and souls: clear, tinted, or opaque today? -- Appendix: a note on values: neither technophobe nor technophile